Harnessing the potential of lipid-based nanomedicines for type-specific ovarian cancer treatments. (March 2014) - Leung, Ada WY; Kalra, Jessica; Santos, Nancy Dos; Bally, Marcel B; Anglesio, Michael S
Epithelial ovarian cancers are a group of at least five histologically and clinically distinct diseases, yet at this time patients with these different diseases are all treated with the same platinum and taxane-based chemotherapeutic regimen. With increased knowledge of histotype-specific differences that correlate with treatment responses and resistance, novel treatment strategies will be developed for each distinct disease. Type-specific or resistance-driven molecularly targeted agents will provide some specificity over traditional chemotherapies and it is argued here that nanoscaled drug delivery systems, in particular lipid-based formulations, have the potential to improve the delivery and specificity of pathway-specific drugs and broad-spectrum cytotoxic chemotherapeutics. An overview of the current understanding of ovarian cancers and the evolving clinical management of these diseases is provided. This overview is needed as it provides the context for understanding the current role of drug delivery systems in the treatment of ovarian cancer and the need to design formulations for treatment of clinically distinct forms of ovarian cancer.